P541Cardiac resynchronization therapy: left or non-left bundle branch block? That is the question. (18th June 2020) - Aguiar Ricardo, I; Nunes-Ferreira, A; Rigueira, J; Rodrigues, T; Cunha, N; Antonio, P S; Morais, P; Pereira, S C; Bernardes, A; Santos, I; Magalhaes, A; Neves, H; et al.
Abstract: Introduction: Cardiac resynchronization therapy (CRT) is associated with reduced mortality and improved quality of life in patients (pts) with low ejection fraction (EF) and conduction delays. Patients with left bundle branch block (LBBB) seem to be the ones who benefit the most from CRT and there is controversy about its efficacy in patients with non-LBBB. Purpose: To compare the prognostic impact and the response rate to CRT in patients with LBBB and non-LBBB. Methods: Prospective single-center study of patients who implanted CRT between 2015 and 2019. Clinical, electrocardiographic and echocardiographic evaluations were made before CRT implant and between 6-12 months post-implant. Patients with EF elevation ≥ 10% or left ventricle end-systolic volume (ESV) reduction ≥ 15% were classified as responders. Patients with EF elevation ≥ 20% or LV ESV reduction ≥ 30% were classified as super-responders. All the parameters were compared between patients with or without LBBB. Prognostic impact of resynchronization therapy was evaluated by comparing total mortality using the Cox regression and Kaplan-Meier methods. Results: From 2015-2019, 566 CRTs were implanted (26.1% female, 72 ± 10.2 years old, follow-up duration 18.9 ± 15.8 months). From these patients, 59% had LBBB (69% males, mean age 71.6 ± 10.8 years, 34.5% ischemic, EF < 30% in 65.5%). The cardiovascular risk factors and comorbidities were similar in both populations (with and without LBBB), except for diabetes which was more frequent in non-LBBB patients (33% vs 50.6%, p = 0.007). Mean duration of QRS was similar between LBBB vs non-LBBB patients (163 ± 19ms vs 160 ± 22ms, p = NS) and baseline ejection fraction was also equivalent (29.8 ± 13.6% vs 27.9 ± 8.9%). The prevalence of complications and surgical revisions were similar in both groups. The response rate according to left ventricle remodelling criteria was higher in LBBB pts (65.9% vs 49.1%, p < 0.05), but the super-responders were similar in both groups (32.5% vs 26.4% p = NS). The 4-year survival rate of patients with LBBB and non-LBBB was similar (86.5% vs 85.3%). Conclusion: In our population the response rate to CRT was higher in LBBB pts. However, and despite the actual controversy about the efficacy of CRT in non-LBBB, the long-term mortality was similar in patients with or without LBBB.